Radio Caos: resistance and cultural experimentation in the 1980s - Guerra, Paula (2019)
The 1980s are crucial to the social, cultural, and political transformations in consolidating culture and establishing a mass entertainment industry in Portugal. It was in this decade that the consolidation of youth cultures occurred and subcultural identities were enhanced. We consider it valuable to understand the (counter) cultural activities surrounding the pirate radio stations that were operated in that decade by a group of young people dissatisfied with the universe of cultural possibilities existing in Portugal – a discontent that was even more pronounced in the city of Porto (Portugal) through Radio Caos’ broadcasts. We propose to study this radio station – called “pirate” – that was active from 1982 to 1988 as a paradigm of cultural, artistic, and musical change, mobilized by the youth of the time.